The Effect of Foreign Investment (PMA), Domestic Investment (PMDN), and Government Expenditure on Gross Regional Domestic Product (GRDP) of East Lombok Regency in 2013-2022 - Suhartini, Suhartini; Hailuddin, Hailuddin; Eka Agustiani (Tinta Emas Institute, 2023)
This study aims to determine and analyze the effect of PMA, PMDN, and government spending on GRDP in East Lombok Regency, both partially and simultaneously. This study uses time series data with a 10-year observation period from 2013-2022. The data in this study are secondary data obtained from the Central Statistics Agency (BPS) and the Investment and One-Stop Integrated Service Office (DPMPTSP) of East Lombok Regency. The analysis method used is multiple linear regression (Ordinary Least Square) which is processed with eviews-12 software. The results showed that partially the FDI and PMDN variables in East Lombok Regency had no significant effect on GRDP growth during the study period, while Government Expenditure had a significant effect. Furthermore, simultaneously the PMA, PMDN and Government Expenditure variables have a significant effect on GRDP growth.